1998
DOI: 10.1074/jbc.273.44.29241
|View full text |Cite
|
Sign up to set email alerts
|

The Plasminogen Binding Site of the C-Type Lectin Tetranectin Is Located in the Carbohydrate Recognition Domain, and Binding Is Sensitive to Both Calcium and Lysine

Abstract: Tetranectin, a homotrimeric protein belonging to the family of C-type lectins and structurally highly related to corresponding regions of the mannose-binding proteins, is known specifically to bind the plasminogen kringle 4 protein domain, an interaction sensitive to lysine. Surface plasmon resonance and isothermal calorimetry binding analyses using single-residue and deletion mutant tetranectin derivatives produced in Escherichia coli showed that the kringle 4 binding site resides in the carbohydrate recognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 28 publications
4
52
1
Order By: Relevance
“…The binding of TN to Plg K4 is mediated by the CTLD of TN, and each TN trimer has three binding sites, one on each protomer (23). We have identified the residues Lys-148, Glu-150, and Asp-165 to be of primary importance for this interaction (23). All three residues are located in the loop region of TN, which also mediates calcium binding.…”
Section: Tetranectin (Tn)mentioning
confidence: 97%
See 1 more Smart Citation
“…The binding of TN to Plg K4 is mediated by the CTLD of TN, and each TN trimer has three binding sites, one on each protomer (23). We have identified the residues Lys-148, Glu-150, and Asp-165 to be of primary importance for this interaction (23). All three residues are located in the loop region of TN, which also mediates calcium binding.…”
Section: Tetranectin (Tn)mentioning
confidence: 97%
“…TN binds to Plg K4, and binding is sensitive to both lysine and calcium (2,23). TN binding involves at least one amino acid * The present work was supported by Grant 9901966 from the Danish Natural Science Research Council.…”
Section: Tetranectin (Tn)mentioning
confidence: 99%
“…SDS\PAGE staining intensities for rTN and mutants confirmed that the use of a rTN A" % " cm,#)! of 20 g:litre −" :cm −" [13] was justifiable for the determination of protein concentration. For rTRIP-A an A" % " cm,#$& of 8 g:litre −" :cm −" was estimated by amino acid analysis.…”
Section: Figure 2 Heparin-sepharose Chromatographymentioning
confidence: 99%
“…The mature TN monomer, of 181 amino acid residues and containing three internal disulphide bridges, is encoded by three exons [8,12], of which the polypeptide encoded by exon 2 is necessary and sufficient for trimerization [1]. The Plg kringle-4-binding site is located within the domain encoded by exon 3 [13], which encodes a domain similar with the carbohydrate recognition domains (CRDs) of the C-type lectin superfamily [14]. TN exhibits pronounced structural similarity to both the neck region and the CRD of the collectins, and binds Ca# + in a similar way [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation